Urban challenges to food and nutrition security: a review of food security, health, and caregiving in the cities - Ruel, Marie T.; Garrett, James L.; Morris, Saul Sutkover; Maxwell, Daniel G.; Oshaug, Arne; Engle, Patrice L.; Menon, Purnima; Slack, Alison T.; Haddad, Lawrence James (International Food Policy Research Institute, 1998)
This review of recent literature explores the urban face of food and nutrition security in a more comprehensive, integrated way than most previous efforts. The review is organized around a conceptual framework that identifies food insecurity, inadequate caring behaviors, and poor health as the primary causes of malnutrition. It discusses current knowledge in eight areas that require the special attention of policymakers, development practitioners, and program administrators who wish to improve urban food and nutrition security: the sources and cost of food; incomes and employment; urban agriculture; urban diets; child caregiving practices; childhood mortality, morbidity, and malnutrition; health and environment; and social assistance programs, or safety nets. The review also reports on the magnitude of rural-urban and intra-urban health differences in mortality, morbidity, and malnutrition. In conclusion, the review indicates which policy issues and knowledge gaps remain for future research to address.